HOW PROCESS APPROACH WORKS IN ARGUMENTATIVE WRITING - Yahmun, Yahmun; Widiyanah, Ima (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The teaching of English writing skills at the college level centers much on non-fiction or scientific writing skills. This is certainly due to the importance of writing a scientific work in the form of essays, articles, final assignment papers and thesis for a student (Anderson, 2009). Of the many types of writing, writing an argumentative essay turns into an academic prima donna for college students since it is able to train them thinking more critically. By habitually writing argumentative writing, a student's sensitivity to opinions and controversial issues around him is more honed. Styslinger (2014) says that writing or argumentative essays are more of an interest in the game of logic, which then involves the claims, facts, justifications and arguments against a thing. The present study elaborates an approach to writing an argumentative essay which is simply known as a process approach. A process approach is aiming students stay focus on steps of writing since the approach provides chronological order. This study later contributes to number of knowledge of writing and academic references for students of English.